STUDYING THE FACTORS EFFECTING THE PRODUCTION OF OKRA PROTEIN CONCENTRATE AND ISOLATE AND THEIR THERMAL PROPERTIES - & Shakir, Kareem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The current study was included the use of okra seeds (Abelmoschus esculentus) for preparation of Defatted Okra Powder (DOP), Okra Protein Concentrate (OPC) and Okra Protein Isolate (OPI). Three methods were used to identify the best one for protein concentrate preparation . The concentrate with 72.1% protein was prepared by removal of seed peel, ground, defatting and treated with ethanol. The optimum conditions for  protein isolate preparation were 1:40 (water: DOP), extraction time of 75 minutes, extraction pH 9.0 and the precipitation pH was  4.0. This study also investigated the chemical composition to products that were 50.8,72.1,91.2% protein ,0.88,0.86,0.32 % fat ,8.45,9.94,2.67% ash and 35.23,12.37,3.26% carbohydrates For each of DOP ,OPC and OPI respectively. The amount of energy required for protein denaturation were 1.193, 0.5325, 0.236 J / g for DOP , OPC and OPI respectively.